Article Evaluation of chemical and sensory composition of banana with cinnamon liqueur: effect of storage process - NASCIMENTO, Gicele Santos do; BORGES, Gabriela Ramos; SCHEID, Camila; GARAVAGLIA, Juliano (Food Science and Technology, 2023)
Banana (Musa sp.) fruits present a high sensory quality and are a source of sugars, minerals, vitamins, and pleasant aroma and flavor and represent a valuable raw material to liqueur production. The aim of this study was to investigate differences in the sensory, chemical, and characteristics of banana liqueurs elaborated by different concentrations of cinnamon (0.25, 0.5, and 0.75%), added as powder and bark form. The cinnamon (Cinnamon cassia) was used to improve the taste and aroma of liqueurs, verifying its effect after storage for 3 months in dark conditions. Physicochemical parameters were evaluated during the storage period of 3 months even as the colorimetric analysis and the sensory profile (assessed through quantitative descriptive analysis). All formulations tested showed parameters according to Brazilian legislation. The addition of cinnamon, mainly in powder and at a level of 0.75%, improves the banana liqueur sensory perception, in terms of taste and aroma, even after 3 months of storage.